Evaluation of Soil Pollution by Some Heavy Metals Via Atomic Absorption Spectrophotometer (AAS) Technique in Zakho District, Kurdistan Region - Iraq - Jindy, Jindy M.; Qasim, Amin K.; Mohamad, Sagvan A. (Science Journal of University of Zakho, 2020)
In this study, the atomic absorption spectrophotometer (AAS) technique has been used in analysing 26 soil samples for five heavy metals: Pb2+, Cu2+, Zn2+, Cr3+ and Ni2+ in Zakho district, Kurdistan region - Iraq. Heavy metals can be accrued to the soil during the releases of industrial waste, removal of extraordinary quality metal waste, petrochemical falls and etc. In all soil samples, heavy metals concentration was found in the range of 0.541 - 4.339 mg/L for Pb, 0.118 - 0.797 mg/L for Cu, 1.260 - 5.540  mg/L for Zn, 1.315 - 2.102 mg/L for Cr and 1.049 -1.635 mg/L for Ni. As shown in the result, the heavy metals concentration contents increases with fossil fuel combustion, industrial releases, and agricultural activities. However, the results of the AAS technique was found that the high concentration element Pb and Zn were determined than the other elements like Cu, Cr and Ni but less than acceptable limits in all cases. Regarding to achieve data in the recent research, soil of case study can be relatively considered unpolluted, healthy and it is suitable for growth plants and usable for other purposes.
Keywords: Heavy metals; Soil; Atomic absorption spectrophotometer (AAS); Zakho district